2018
DOI: 10.1016/j.amsu.2018.08.010
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of prognostic factors associated with recurrence or metastasis of gastrointestinal stromal tumor (GIST) of stomach

Abstract: BackgroundGastrointestinal stromal tumor (GIST) is the most common mesenchymal neoplasm of the gastrointestinal tract. The major risk factors of recurrence and metastasis are mitotic index and tumor size. This study investigates the risk of recurrence and metastasis in solely gastric GIST. The primary outcome is to evaluate risk of recurrence and metastasis. The secondary outcome is to analyse survival rates of patients who have recurrence and metastasis after curative resection.MethodA cohort of patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
(22 reference statements)
2
9
1
Order By: Relevance
“…This study was dedicated to building a comprehensive scoring system and made up for these shortcomings. Meanwhile, most studies estimated the metastatic risk of GIST based on tumor location, tumor size, and mitotic count but ignored some other features of tumor [2,7,8]. Our nomogram showed that small intestine held the highest metastatic risk.…”
mentioning
confidence: 90%
“…This study was dedicated to building a comprehensive scoring system and made up for these shortcomings. Meanwhile, most studies estimated the metastatic risk of GIST based on tumor location, tumor size, and mitotic count but ignored some other features of tumor [2,7,8]. Our nomogram showed that small intestine held the highest metastatic risk.…”
mentioning
confidence: 90%
“…While most GISTs are found in the stomach, 20% to 30% are present in the small intestine, 5% to 15% present in the colon, and less than 5% present in the esophagus and other regions [ 8 , 14 , 15 , 16 ]. Although the only principal treatment of localized GISTs is surgical resection with negative margins, there is a risk for recurrence or metastasis; one cohort study reported that 29.4% of cases showed recurrence or metastasis following curative resection of gastric GISTs during a median 31.95 months of follow-up [ 17 ]. Our study revealed a lower recurrence rate of 2.7%, which may be the result of bias due to our small sample size and inclusion of only patients with gastric GISTs who underwent curative surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that metastasis correlated with tumor size > 10 cm ( P = 0.023) and mitotic count > 5/5 mm 2 ( P = 0.000). In the study of Supsamutchai et al[ 15 ], they demonstrated that there were significant differences between mitotic index or tumor size and the risk of recurrence or metastasis ( P = 0.036). Our data demonstrated that tumor location was also an important factor affecting recurrence.…”
Section: Discussionmentioning
confidence: 99%